Cause‐specific mortality of the world's terrestrial vertebrates. Issue 5 (30th January 2019) - Hill, Jacob E.; DeVault, Travis L.; Belant, Jerrold L.
Abstract: Aim: Vertebrates are declining worldwide, yet a comprehensive examination of the sources of mortality is lacking. We conducted a global synthesis of terrestrial vertebrate cause‐specific mortality to compare the sources of mortality across taxa and determine predictors of susceptibility to these sources of mortality. Location: Worldwide. Time period: 1970–2018. Major taxa studied: Mammals, birds, reptiles and amphibians. Methods: We searched for studies that used telemetry to determine the cause of death of terrestrial vertebrates. We determined whether each mortality was caused by anthropogenic or natural sources and further classified mortalities within these two categories (e.g. harvest, vehicle collision and predation). For each study, we determined the diet and average adult body mass of the species and whether the study site permitted hunting. Mortalities were separated into juvenile or adult age classes. We used linear mixed effects models to predict the percentage of mortality from each source and the overall magnitude of mortality based on these variables. Results: We documented 42, 755 mortalities of known cause from 120, 657 individuals representing 305 vertebrate species in 1, 114 studies. Overall, 28% of mortalities were directly caused by humans and 72% from natural sources. Predation (55%) and legal harvest (17%) were the leading sources of mortality. Main conclusions: Humans were directly responsible for more than one‐quarter of global terrestrial vertebrate mortality. Larger birds and mammals were harvested more often and suffered increased anthropogenic mortality. Anthropogenic mortality of mammals and birds outside areas that prohibited hunting was higher than within areas where hunting was prohibited. Mammals experienced shifts from predominately natural to anthropogenic mortality as they matured. Humans are a major contributor to terrestrial vertebrate mortality, potentially impacting evolutionary processes and ecosystem functioning.